Proceedings of the 3rd International Web Science Conference 2011
DOI: 10.1145/2527031.2527052
|View full text |Cite
|
Sign up to set email alerts
|

Bad news travel fast

Abstract: On the microblogging site Twitter, users can forward any message they receive to all of their followers. This is called a retweet and is usually done when users find a message particularly interesting and worth sharing with others. Thus, retweets reflect what the Twitter community considers interesting on a global scale, and can be used as a function of interestingness to generate a model to describe the content-based characteristics of retweets. In this paper, we analyze a set of high-and low-level content-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(47 citation statements)
references
References 10 publications
3
44
0
Order By: Relevance
“…Hashtags facilitate formation of ad-hoc groups interested in specific topics or events 42 and are positively associated with audience engagement (i.e., retweeting). 43,44 We used online tools (e.g., hashtagify.me) to identify hashtags specific to childhood obesity and found two: #childhoodobesity and #childobesity. Due to low use of #childobesity, we selected #childhoodobesity as our only search term.…”
Section: Methodsmentioning
confidence: 99%
“…Hashtags facilitate formation of ad-hoc groups interested in specific topics or events 42 and are positively associated with audience engagement (i.e., retweeting). 43,44 We used online tools (e.g., hashtagify.me) to identify hashtags specific to childhood obesity and found two: #childhoodobesity and #childobesity. Due to low use of #childobesity, we selected #childhoodobesity as our only search term.…”
Section: Methodsmentioning
confidence: 99%
“…Albeit, another surprising outcome is that actively using Twitter was related to lower satisfaction with life (H4 partially supported). Previous studies have shown that negative messages are shared faster on Twitter (Naveed, Gottron, Kunegis, & Alhadi, 2011) and that popular events on Twitter are associated with negative emotions (Thelwall, Buckley, & Paltoglou, 2011). Recently, Waterloo, Baumgartner, Peter and Valkenburg (2018) showed than negative emotions are perceived as more appropriate on Facebook and Twitter compared to Instagram.…”
Section: Various Snss and Well-being 14mentioning
confidence: 99%
“…The "retweet" functionality and the retweet counter can be considered as a factor for measuring the "interestingness" of a user's tweets [33]. Based on that, the resulting spread of information is examined in [11].…”
Section: Diffusion-oriented Approachesmentioning
confidence: 99%